2017
DOI: 10.18203/2320-1770.ijrcog20175859
|View full text |Cite
|
Sign up to set email alerts
|

A study on risk factors, maternal and foetal outcome in cases of preeclampsia and eclampsia at a tertiary care hospital of South India

Abstract: INTRODUCTIONHypertension in pregnancy remains still a major health issue for women and their descendants throughout the world but remains a major issue in developing countries rather than developed countries. Globally preeclampsia [PE] and eclampsia are responsible for approximately 14% of maternal deaths with variable incidences in developed and developing countries.1 Eclampsia accounts for 24% of maternal deaths during pregnancy in India according to FOGSI study in India.2 Gestational hypertension affects 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
2
3
1
1
Order By: Relevance
“…Rate of complications depends upon number of convulsions, duration of convulsion, duration of admission between hospitalization and last fit, proper nursing care treatment, least time for delivery. The incidence of maternal mortality in our study was 5% which is in line with study conducted by Shailja B et al 21 (4.64%). Other studies had reported higher mortality rate of around ten percent.…”
Section: Discussionsupporting
confidence: 92%
“…Rate of complications depends upon number of convulsions, duration of convulsion, duration of admission between hospitalization and last fit, proper nursing care treatment, least time for delivery. The incidence of maternal mortality in our study was 5% which is in line with study conducted by Shailja B et al 21 (4.64%). Other studies had reported higher mortality rate of around ten percent.…”
Section: Discussionsupporting
confidence: 92%
“…11 Sailja et al on the other hand found maximum cases of preeclampsia in >35 years age group (46%) and eclampsia in 26-35 years group (20.5%). 5 Similarly, our results of 57.94% preeclampsia cases in nulliparous women is similar to 45.9% reported by Bej et al and 63.3% of nulliparous hypertensive cases reported by Bal et al 4,11 We didn't find either of these age groups or nulliparity to have statistically significant association with increased probability of adverse maternal or fetal outcome. So, although maternal age and parity may help us predict a risk of preeclampsia, they are not significant prognostic markers.…”
Section: Discussionsupporting
confidence: 88%
“…4 Sailaja reported 2.1% incidence of hypertensive disorders of which 54.1% were preeclampsia and eclampsia. 5 The reported incidence in these studies is much less than the incidence of hypertensive disorders in our study which was 11.85% for hypertensive disorders and 6.18% for severe preeclampsia and eclampsia.…”
Section: Discussioncontrasting
confidence: 59%
“…WHO has estimated the incidence of preeclampsia to be seven times higher in developing countries (2.8% of live births) than in developed countries (0.4%) 3 . In developing countries like India, about 50% of GH leads to preeclampsia, which may culminate in eclampsia if not treated early and effectively 4 . The maternal mortality in eclampsia in India is estimated to be 20–33% 5 .…”
Section: Introductionmentioning
confidence: 99%